"PER MODUM QUIETIS": LA CONOSCENZA DI MARIA TRA "RAPTUS" ED "ECSTASIS" NEL SERMO VI DE ASSUMPTIONE BEATAE VIRGINIS MARIAE ATTRIBUITO A BONAVENTURA. - Chiti, Elisa (Revista Española de Filosofía Medieval, 2022)
An analysis of the boundary between "raptus", "ecstasis" and "excessus mentis" allows us to draw a line that unites theology and speculative mysticism, with interesting results. The mystical state described with regard to the co-redemptrix Virgin in Sermo VI de assumptione beatae Virginis Mariae constitutes a good starting point. I will analyze the fundamental characteristics of the peculiar charism of the Virgin Mary "in via", which overcomes the knowledge of the prophets and makes her deiform, perfectly coinciding in knowledge with the Son being by her proper ontological and gnoseological "status" co-redemptive of humanity, a heavenly door between man and God.